2021
DOI: 10.3390/ijerph18073568
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Trauma and African Americans’ Mental Health: Seizing Opportunities for Transformational Change

Abstract: The COVID-19 pandemic is a natural disaster of historic proportions with widespread and profound psychological sequelae. African Americans fall ill and die more than whites from COVID and more survivors and loved ones face psychological risk. African Americans also experience greater personal, social, and financial stress even when not personally touched by COVID illness, and they are again vulnerable as COVID diminishes African American community’s capacity for mutual support. Enactment of the American Rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Mental wellbeing has continued to deteriorate over the past few years among minority populations in the US, including Blacks/African Americans [ 12 ]. Our findings corroborate others that demonstrate that the COVID-19 pandemic worsened the pre-existing inequities in mental health [ 13 ]. Access to mental health services was further limited while pre-existing conditions were exacerbated by stressors related to health concerns and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 91%
“…Mental wellbeing has continued to deteriorate over the past few years among minority populations in the US, including Blacks/African Americans [ 12 ]. Our findings corroborate others that demonstrate that the COVID-19 pandemic worsened the pre-existing inequities in mental health [ 13 ]. Access to mental health services was further limited while pre-existing conditions were exacerbated by stressors related to health concerns and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, the emerging syndemic of COVID-19, health inequities, and racism has yielded poor outcomes in health, economics, and social wellness, which has exacerbated poor mental health among African Americans [ 51 ]. We found that almost all participants were experiencing stress on some level with women having higher stress levels, reflecting studies emerging in the literature [ 17 , 33 , 52 , 59 ]. Because women naturally experience more stress and anxiety compared to men, the COVID-19 pandemic may be exacerbating this difference [ 12 , 21 ].…”
Section: Discussionsupporting
confidence: 81%
“…They are also more likely to be threatened by reductions in pay or hours, temporary furloughs, or permanent layoffs [ 35 ]. Collectively, this syndemic—COVID-19 pandemic, racism, and “structural inequity”—contributes to psychosocial distress in marginalized communities and has prompted the opportunity for a transformational change [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…They underscore the intensity of the situation for the Black community, the pernicious intersections of impoverished living conditions, lack of access, stigmatization, and a history of mistrust of the health care system rooted in hundreds of years of mistreatment. All these factors contribute to making African Americans the most adversely affected population in the United States in terms of deaths, anxiety levels, and burdens of care (Snowden and Snowden 2021).…”
Section: "We Were Already In a Crisis": Covid-19 In The Afican Americ...mentioning
confidence: 99%